Chimney Endografting for Pararenal Aortic Pathologies Using Transfemoral Access and the Lift Technique. (August 2013) - Lachat, Mario; Bisdas, Theodosios; Rancic, Zoran; Torsello, Giovanni; Mayer, Dieter; Gil-Sales, Josep; Pecoraro, Felice; Donas, Konstantinos P.
Purpose: To present a technique for transfemoral implantation of parallel grafts into the renal arteries in patients with anatomy or morphology that blocks standard antegrade chimney graft delivery. Technique: In a totally percutaneous approach, a 5-F pigtail angiographic catheter is passed into the aorta above the renal arteries via a 0.035-inch hydrophilic guidewire, followed by an 8-F sheath. The target vessel is cannulated with the hydrophilic wire followed by a 5-F reverse curve catheter; the wire is changed for a Rosen wire. The main stent-graft body is delivered and parked at the level of the aortic bifurcation. The Viabahn chimney endograft is advanced ∼1 to 2 cm into the target renal artery and deployed such that its proximal end faces downward; its distal end is fixed in place with an inflated angioplasty balloon. A stiff guidewire is inserted coaxially through the 8-F sheath, the Rosen guidewire is removed, and the 8-F sheath is carefully pushed over the stiff guidewire, lifting the sheath and chimney endograft upward. With the chimney reoriented cranially, the aortic stent-graft is deployed immediately. The abdominal stent-graft and the chimney graft(s) are molded synchronously using kissing balloons. Conclusion: Transfemoral placement of chimney covered stents by the lift technique in cases of unsuccessful or hazardous catheterization of the target vessels via the upper extremity is safe and feasible in centers experienced with the standard chimney technique.